PENERAPAN MODEL PEMBELAJARAN IKRAR (INISIASI, KONSTRUKSI-REKONSTRUKSI, APLIKASI, REFLEKSI) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI MIA SMA NEGERI 9 PEKANBARU - Nurul Hanifah; Johni Azmi; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research is to know the improvement of student learning result by implementing IKRAR learning model (Initiation, Construction-Reconstruction, Aplication, Reflection) on the chemical equilibrium subject in the class XI MIA SMAN 9 Pekanbaru. This research is experimental research using Design Randomized Control Group Pretest-Posttest. The research sample consisted of two classes, class XI MIA 1 as experiment class and class XI MIA 3 as control class that has tested by normality test using Liliefors test and homogeneity test using equality of two average test. Hypothesis was done by using right side t-test. Research result shown that the implementation of IKRAR learning model can improve student learning result on the chemical equilibrium subject where tarithmetic = 2,25 > ttable = 1,67.Key Words: IKRAR learning model (Initiation, Construction-Reconstruction, Aplication, Reflection), Learning Result, Chemical Equilibrium